(untitled) (Journal of Partial Differential Equations, 2021)
By means of the Banach fixed point principle, we establish some sufficient conditions ensuring the existence of the global attracting sets and the exponential decay in the mean square of mild solutions for a class of neutral stochastic functional differential equations by Poisson jumps. An example is presented to illustrate the effectiveness of the obtained result.